Determining the value of Māori nurses in Aotearoa : a thesis presented in partial fulfilment of the requirements for the degree of Masters of Business Studies (Management), School of Management, Massey University, Palmerston North, New Zealand - Te Whata, Tracy Deborah (Massey University, 2020)
This thesis examines the experiences of Māori Registered nurses within Aotearoa, New Zealand. This research offers an understanding of how Nursing discourse is embedded within legislation, regulatory bodies, and nursing practice and its direct impact on the health and well-being of Māori nurses. This discourse continues to marginalise and undervalue tikanga. As Māori nurse’s workplace expectations of cultural responsibilities are undertaken over and above standard nursing practices. Māori nurses often get allocated what was coined ‘difficult’ or complex Māori patient and their whānau. Māori nurses must ensure whānau are kept culturally safe while navigating and advocating for whānau in health care organisations where 1 in 2 Māori nurses face racism and discrimination. This thesis explored the experiences of Māori registered nurses using a kaupapa Māori, mixed-method approach. The survey was distributed during a two-week period during Covid-19. Five semi-structured interviews were completed, and responses were used to inform a survey of which there were 342 respondents. Once the data was cleaned, 333 valid responses were used to examine the perspective of Māori Registered nurses. Also identified were the experiences of Māori nurses and the impact on career advancement, use of tikanga in practice, cultural identity, professional development, and racism and discrimination within their work environment. This thesis’s findings validated the lack of leadership, opportunities, and responsive practices required to ensure Māori nurses are supported and valued not only within their profession but within their organisations honouring Te Tiriti o Waitangi requires creating real change for Māori nursing professionals to ensure they feel valued in their workplace, are fairly remunerated, and feel safe to identify and practice as Māori within their workplace.
Keywords: Māori nurses; valuing Māori culture; cultural competency; discrimination; racism; professional accountability; Māori Masters Thesis; 451012 Te mahi tapuhi o te Māori (Māori nursing); 420505 Nursing workforce